Microfluidic 3D cell culture: potential application for tissue-based bioassays. (June 2012) - Li, XiuJun (James); Valadez, Alejandra V; Zuo, Peng; Nie, Zhihong
Current fundamental investigations of human biology and the development of therapeutic drugs commonly rely on 2D monolayer cell culture systems. However, 2D cell culture systems do not accurately recapitulate the structure, function or physiology of living tissues, nor the highly complex and dynamic 3D environments in vivo . Microfluidic technology can provide microscale complex structures and well-controlled parameters to mimic the in vivo environment of cells. The combination of microfluidic technology with 3D cell culture offers great potential for in vivo -like tissue-based applications, such as the emerging organ-on-a-chip system. This article will review recent advances in the microfluidic technology for 3D cell culture and their biological applications.